Stress and obligativity of police officers - Călin, Mariana Floricica; Rus, Mihaela; Sandu, Mihaela Luminita (Technium Social Sciences Journal, 2021)
In the present study, I examined the differences between criminal police officers and border police officers. The study shows if there are any semnificative differences of stress and mentality for the two types of policemen. 2 tests were applied on 60 participants, 30 of each category. One test was for measuring stress and the other one for observing the mentality of the employees. The study has 2 hypotheses: the presumtion that there are semnificative differences of stress between the two types of officers and the presumtion that there are semnificative differences between levels of obligativity for the two types of officers. The hypotheses were confirmed.